2013
DOI: 10.1155/2013/534342
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Airborne Transmission of Porcine Postweaning Multisystemic Wasting Syndrome

Abstract: The objective of these studies was to investigate if porcine postweaning multisystemic wasting syndrome (PMWS) could be induced in healthy pigs following contact with air from pigs with clinical signs of PMWS. The pigs were housed in different units. Either 31 (study I) or 25 (study II) pigs with clinical symptoms of PMWS from a PMWS-affected herd and 25 healthy pigs from a PMWS-free, but PCV2-positive, herd were housed in unit A. Fifty pigs from a PMWS-free herd were housed in unit B, which were connected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Apart from the oronasal route, which is the most likely means of horizontal transmission [ 82 ], other potential routes of PCV2 transmission are the nose-to-nose route [ 174 ] and fecal–oral route [ 175 ]. Surprisingly, not only the virus but also PMWS showed the potentiality of transmission from PMWS-affected pigs to healthy, unaffected pigs through direct contact or indirect airborne contact [ 176 , 177 ]. The virus might be present in nasal secretion, trachea-bronchial secretion, blood, urine, faces, oral fluid, milk, and semen [ 178 , 179 , 180 , 181 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%
“…Apart from the oronasal route, which is the most likely means of horizontal transmission [ 82 ], other potential routes of PCV2 transmission are the nose-to-nose route [ 174 ] and fecal–oral route [ 175 ]. Surprisingly, not only the virus but also PMWS showed the potentiality of transmission from PMWS-affected pigs to healthy, unaffected pigs through direct contact or indirect airborne contact [ 176 , 177 ]. The virus might be present in nasal secretion, trachea-bronchial secretion, blood, urine, faces, oral fluid, milk, and semen [ 178 , 179 , 180 , 181 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%
“…Initial analysis showed that E. coli, Enterococcus spp., somatic coliphages, HEV, PCV2 and RV-A were present in the pig slurry and they were therefore all selected for analysis in the leaching study (Table 1). Porcine circovirus type 2 (PCV2) was included as this virus is ubiquitous in swineherds and highly persistent in the farm environment (Kristensen et al 2013). Drainage water was sampled flow-proportionally (Plauborg et al 2003; ISCO 6700 sampler, Teledyne Isco Inc., US).…”
Section: Sampling Of Pig Slurry and Drainage Watermentioning
confidence: 99%